Changes in Corneal Dendritic Cell and Sub-basal Nerve in Long-Term Contact Lens Wearers With Dry Eye. Issue 4 (July 2020) - Liu, Qiaoli; Xu, Zhiqiang; Xu, Yangyang; Zhang, Junsong; Li, Yong; Xia, Jiahui; Wang, Yuzhou; He, Xiaoxing; Qu, Jia; Hu, Liang
Abstract : Objectives: To evaluate the changes of corneal sub-basal nerve (SBN) and dendritic cell (DC) in contact lens (CL) wearers with mild dry eye and their potential relationship. Methods: Twenty mild dry eye volunteers who had never worn CLs were recruited for long-term CL wearing. Each subject underwent ocular surface evaluations at baseline and at 1, 4, 12, and 24 weeks, including Ocular Surface Disease Index (OSDI) questionnaire, tear film break-up time (TBUT), and Schirmer I test. In vivo confocal microscopy was used to examine the density, area, number of dendrites, total dendritic length of DC, and SBN densities in central and peripheral corneas. Only right eyes were included. Results: The DCs were activated and peaked at week 4 after wearing CLs. The peripheral DC density increased beginning the first week, whereas the central ones increased by week 4. After 4 weeks, both began to decrease, but still higher than baseline at week 24. The central and peripheral SBN densities decreased. However, the peripheral SBN tended to increase beginning at week 12. In early period, SBN was negatively correlated with DC parameters. After 4 weeks, the correlation changed to be positive. The OSDI increased, whereas the Schirmer I test and TBUT showed no significant change. Conclusions: After wearing CLs, corneal DC were activated and increased, indicating ocular surface inflammation and decreased after week 4. In the early period, increases in DC may lead to decreases in SBN. Upon decrease of DC, the SBN may regenerate.